Profitability difference between listed bank and non-listed bank - Edi, Edi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze what factor that can affect the profitability of listed bank and non-listed bank. The impact factor are internal and external factors. The detail of internal factors of the bank consist of bank size, capital adequacy ratio, management efficiency, diversification income, liquidity risk, credit risk and external factors of bank consist of market concentration, inflation and gross domestic product. Measurement of bank profitability that used on this study is net interest margin. The sample of this research is banks that are listed in OJK consist of 42 public owned banks and 63 private owned banks. The research data are tested and analyzed with data panel regression using E-views. The results of this research prove that management efficiency, liquidity risk, and market concentration are giving a significant effect to bank profitability. The novelty of this research are approaching the different result between listed bank and non-listed bank profitability in order to find out whether there are different factor that are influencing listed bank and non-listed bank profitability.